Estudo de caso para a viabilidade de implementação de sistema de tratamento de esgoto compacto na região metropolitana de Goiânia - Haraguchi, Marcelo Tsuyoshi (2014)
The aim of this study is to assess the feasibility of a system of ETE compact rather than a conventional system of sewage treatment plants already established in the country in the treatment of sewage, considering its cost, efficiency and demand space. Systems compared in this analysis are: ETE Goianira, conventional system; ETE Gold Fields, compact system. The station Gold Fields has not reached the efficiency of the conventional system, but the results are in accordance with what is established by environmental legislation. The ETE is more compact deployment cost and maintenance, but the difference does not make it unfeasible due to return in the occupation of space, which is substantially favorable compared to conventional stabilization ponds ETE Goianira.